Heat-insulating hollow microsphere with high strength as well as preparation method and application of heat-insulating hollow microsphere
By adopting a combined structure of glass sphere shell layer, metal silver layer and island metal oxide layer in hollow microspheres, the challenges of hollow microsphere thermal insulation materials in coordinated control of mechanical strength, thermal conductivity and emissivity are solved, and the combination of high strength, low thermal conductivity and low infrared emissivity is achieved.
Patent Information
- Application Number
- CN202311067861.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-23
- Publication Date
- 2025-02-25
AI Technical Summary
Existing hollow microsphere thermal insulation materials have challenges in the coordinated control of mechanical strength, thermal conductivity and emissivity, especially in low-density hollow microsphere systems.
A hollow microsphere structure consisting of a glass spherical shell layer, a metal silver layer and a metal oxide layer are adopted, wherein the metal oxide layer is composed of an independent island structure with a coverage ratio of between 30-65%, and a glass spherical shell layer with a content of 35-75 wt% of each component, a metal silver layer with a metal oxide layer of 20-50 wt% and a metal oxide layer of 5-15 wt% of the metal oxide layer.
The hollow microspheres have high mechanical stability, low thermal conductivity and low infrared emissivity, avoiding the increase in infrared emissivity caused by the increase in thermal conductivity, and have stable structural properties.
Smart Images

Figure CN119504150A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of powder materials, and more specifically to a high-strength heat-insulating hollow microsphere and a preparation method and application thereof. Background Art
[0002] With the development trend of efficient energy conversion, storage and utilization, the research, development and application of high-efficiency thermal insulation materials have received widespread attention. Thermal insulation materials include foams, porous materials, coatings, powders, heat reflective screens and other forms. Although different application fields have different requirements for thermal insulation materials, under the general trend of lightweight, environmentally friendly and multifunctional development, various application fields have put forward higher and higher requirements for the coordinated design of thermal insulation properties and other physical properties of thermal insulation materials. In order to meet the increasing application requirements, researchers have designed a variety of advanced thermal insulation materials with different chemical compositions and physical structures, among which micron-sized hollow structures (hollow microspheres) with spherical shapes are an important member. Hollow microsphere thermal insulation materials have the following advantages: 1) Low thermal conductivity and low density can be obtained by utilizing the internal cavity; 2) The performance can be greatly controlled by adjusting its structural characteristics (spherical shell thickness, size and size distribution); 3) The spherical shape also gives it high fluidity and filling properties, so that it has good processability when used as a filler (compounded with a matrix material) or as a powder (powder insulation); 4) The spherical shell (all or a layer of a multi-layer spherical shell) can be designed as a dense structure, thereby improving its waterproof and moisture resistance, while reducing the dependence of the high thermal insulation effect on the vacuum degree.
[0003] In view of the above advantages, hollow microsphere structures are highly favored in the design and construction of high-performance thermal insulation materials. In terms of the independent construction of thermal insulation structures by hollow microspheres, researchers have conducted some research on the influence of factors such as the particle size, shell thickness, shell connection state, and external atmosphere of hollow microsphere insulation materials on the thermal conductivity, thermal diffusivity, and heat capacity of the thermal control properties of the hollow microsphere stack. In terms of using hollow microspheres as fillers to construct filler-type thermal insulation composite structures, a series of studies have been conducted on the composite and structural relationship between a variety of different matrices and hollow microspheres. It is worth mentioning that, compared with the pore structure constructed by physical or chemical foaming of the matrix, the existence of the spherical shell of the hollow microsphere not only provides the possibility of optimizing the thermal insulation effect by regulating the spherical shell structure, but also mechanically reinforces the cavity wall of the pore, which is conducive to obtaining a composite thermal insulation material with both thermal insulation effect and mechanical strength. In addition, by compounding hollow microspheres of different sizes and chemical compositions, composite thermal insulation materials based on hollow microspheres can also obtain richer functionality and greater performance regulation space. However, as mentioned above, although as independent powder insulation and filler-type composite insulation, the characteristics of the hollow microspheres themselves play a decisive role in the thermal insulation effect and comprehensive performance of the materials, for current hollow microsphere insulation materials, especially low-density hollow microsphere systems, it is still a great challenge to achieve coordinated control of their mechanical strength, thermal conductivity and emissivity through spherical shell composition and structural design. Summary of the invention
[0004] In view of the deficiency of simultaneous optimization of emissivity and thermal conductivity of lightweight and high-strength hollow microspheres in terms of thermal insulation performance, the object of the present invention is to provide a high-strength thermal insulation hollow microsphere and a preparation method and application thereof.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] On the one hand, the present invention provides a high-strength heat-insulating hollow microsphere, wherein the structure of the hollow microsphere comprises a hollow core, and a glass shell layer, a metal silver layer and a metal oxide layer arranged in sequence from the inside to the outside;
[0007] The metal oxide layer is composed of a plurality of metal oxide regions, and the metal oxide regions are physically isolated from each other to expose a portion of the outer surface of the metal silver layer.
[0008] In the technical solution of the present invention, each metal oxide region is independent of each other and presents an island structure that is not connected to each other. The portion of the metal oxide layer where no metal oxide region exists exposes the undivided outer surface of the metal silver layer.
[0009] It should be noted that in the technical solution of the present invention, the glass spherical shell layer and the metal silver layer are both continuous layer structures.
[0010] Furthermore, in the metal oxide layer, the metal oxide region is selected from one oxide of nickel, cobalt, iron, copper, zinc and aluminum or a mixture of two or more oxides. Preferably, it is nickel oxide. The hollow microspheres obtained at this time have suitable mechanical stability, low thermal conductivity and low emissivity.
[0011] Furthermore, the coverage rate of the metal oxide layer on the surface of the metal silver layer is 30-65%. The hollow microspheres obtained at this time have suitable mechanical stability, low thermal conductivity and low emissivity. In the present technical solution, the coverage rate refers to the ratio of the area of the metal oxide layer covering the surface of the metal silver layer to the total surface area of the metal silver layer. Exemplarily, the coverage rate of the metal oxide layer on the surface of the metal silver layer includes but is not limited to 35-65%, 36-61%, 35-55%, 35-52%, 35-40%, 36%, 37%, 52%, 61%, etc.
[0012] Furthermore, the contents of the components in the hollow microspheres are: 35-75wt% of the glass shell layer, 20-50wt% of the metal silver layer, and 5-15wt% of the metal oxide layer, in terms of mass percentage. The hollow microspheres thus obtained have suitable mechanical stability, low thermal conductivity, and low emissivity.
[0013] Exemplarily, the mass percentage of the glass shell layer in the hollow microspheres is 40-75wt%, 45-75wt%, 45-72wt%, 50-75wt%, 50-72wt%, 71.4wt%, 58.8wt%, 47.6wt%, 40wt%, etc.
[0014] Exemplarily, the mass percentage of the metallic silver layer in the hollow microspheres is 20-45wt%, 21-45wt%, 20-40wt%, 21.4wt%, 35.3wt%, 42.9wt%, 48wt%, etc.
[0015] Illustratively, the mass percentage of the metal oxide layer in the hollow microspheres is 5-12wt%, 7-10wt%, 5-8wt%, 7.2wt%, 5.9wt%, 9.5wt%, 12wt%, etc.
[0016] Furthermore, the density of the hollow microspheres is 0.3-1 g / cm 3 , with an average diameter of 15-80μm.
[0017] For example, the density of the hollow microspheres includes, but is not limited to, 0.3-0.8 g / cm 3 , 0.3-0.5g / cm 3 , 0.38g / cm 3 wait.
[0018] Illustratively, the average diameter of the hollow microspheres includes, but is not limited to, 15-50 μm, 30-50 μm, 40-45 μm, 40-41 μm, and the like.
[0019] It should be noted that the “average diameter” refers to the average diameter of the outer surface of the hollow microspheres.
[0020] In another aspect, the present invention provides a method for preparing the above-mentioned heat-insulating hollow microspheres, the preparation method comprising the following steps:
[0021] The glass hollow microspheres are subjected to surface activation treatment;
[0022] Assembling a metallic silver layer on the surface of the glass hollow microspheres after surface activation treatment to obtain microspheres A;
[0023] A metal oxide layer is formed on the surface of microsphere A.
[0024] In the present technical solution, there is no requirement for the size of the glass hollow microspheres. Preferably, the shell thickness of the glass hollow microspheres is 0.3-2 μm.
[0025] The glass hollow microspheres are preferably used after flotation. The flotation method is: mixing the glass hollow microspheres with water at a volume ratio of 1:4, stirring, standing and separating the layers, taking the upper layer of floating microspheres, filtering, and drying.
[0026] Furthermore, the method for performing surface activation treatment on the glass hollow microspheres comprises the following steps:
[0027] The glass hollow microspheres are placed in a mixture of ethanol and water containing 2-18 g / L 3-aminopropyltriethoxysilane, stirred and mixed at room temperature, filtered, dried, and then heat treated at 100-130° C. for 2-5 h;
[0028] The glass hollow microspheres are then placed in a 15 g / L stannous chloride aqueous solution, stirred and mixed, filtered, and dried.
[0029] Furthermore, the method for performing surface activation treatment on the glass hollow microspheres comprises the following steps:
[0030] The glass hollow microspheres are placed in a mixture of ethanol and water containing 15 g / L 3-aminopropyltriethoxysilane, stirred and mixed at room temperature, filtered, dried, and then heat treated at 120° C. for 3 h;
[0031] The glass hollow microspheres are then placed in a 15 g / L stannous chloride aqueous solution, stirred and mixed, filtered, and dried.
[0032] Through the surface activation treatment, the hollow microspheres obtained subsequently have a stable structure and excellent performance.
[0033] Furthermore, in the mixture of ethanol and water, the volume ratio of ethanol to water is 2:1.
[0034] Furthermore, the glass hollow microspheres are added to the mixed solution at a concentration of 0.3 g / mL.
[0035] Furthermore, the glass hollow microspheres are added to the stannous chloride aqueous solution at a concentration of 30-35 g / L.
[0036] Furthermore, the method of assembling a metallic silver layer on the surface of the glass hollow microspheres after surface activation treatment to obtain microspheres A comprises the following steps:
[0037] The glass hollow microspheres after surface activation treatment were mixed with a treatment solution containing 15 g / L silver nitrate and 8 g / L ammonia water, and then formaldehyde solution was added dropwise to react at room temperature to assemble the silver sphere shell.
[0038] Furthermore, the amount of the glass hollow microspheres after surface activation treatment relative to the treatment liquid is 6-30 g / L.
[0039] Furthermore, the dosage of the formaldehyde solution relative to the treatment liquid is 15-20 g / L.
[0040] Furthermore, the method for forming a metal oxide layer on the surface of microsphere A comprises the following steps:
[0041] The microspheres A are mixed with the reaction solution, and reacted at 400-600° C. for 30 minutes in an air atmosphere to obtain the heat insulating hollow microspheres.
[0042] Illustratively, the reaction temperature includes but is not limited to 450-600°C, 450-550°C, 500°C, etc.
[0043] Furthermore, the reaction liquid contains metal salt, water-soluble organic matter and water, and the mass ratio of the microsphere A to the metal salt, water-soluble organic matter and water is (2-5):(10-15):(6-10):(5-7).
[0044] Furthermore, the metal salt solution is selected from at least one of metal nitrates or metal organic acid salts.
[0045] Furthermore, the water-soluble organic matter is selected from at least one of sucrose, starch and citric acid.
[0046] In the preparation method, preferably, a sieving step is further included after the reaction. The sieving and dispersing method is: the product obtained by the reaction is gently ground and pressed on a 50-300 mesh standard sieve to disperse and pass through the sieve holes.
[0047] In yet another aspect, the present invention provides use of the thermal insulating hollow microspheres as described above in thermal insulation powders and thermal insulation fillers.
[0048] The beneficial effects of the present invention are as follows:
[0049] The heat-insulating hollow microspheres provided by the present invention have both low thermal conductivity and infrared emissivity, and also have low density and high mechanical stability. In the heat-insulating hollow microspheres, the internal cavity realizes the overall density reduction and thermal conductivity reduction of the hollow microspheres; the metal silver material with low infrared emissivity is the second layer of continuous spherical shells, which reduces the emissivity of the spherical shells and mechanically reinforces the hollow structure; the metal oxide with low thermal conductivity reduces the overall thermal conductivity of the microspheres; the unique island-shaped (non-interconnected) metal oxide structural unit reduces the thermal conductivity while avoiding a substantial increase in infrared emissivity (it can avoid the overlap of the metal spherical shells when the hollow microspheres are stacked or filled to form a heat conduction path (thereby causing an increase in thermal conductivity)). In addition, in the heat-insulating hollow microspheres, the setting of each layer structure and the selection of materials make the heat-insulating hollow microspheres have a stable structure. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] The specific implementation modes of the present invention will be further described in detail below in conjunction with the accompanying drawings.
[0051] Figure 1 The schematic diagram of the structure of the heat-insulating hollow microspheres with high strength in the present invention is shown.
[0052] Figure 2 A schematic diagram of the preparation process of the heat-insulating hollow microspheres with high strength in the present invention is shown.
[0053] Figure 3 A low-magnification SEM image of the hollow microspheres prepared in Example 2 is shown.
[0054] Figure 4 A high-magnification SEM image of the hollow microspheres prepared in Example 2 is shown.
[0055] Figure 5 The X-ray diffraction pattern of the hollow microspheres prepared in Example 2 is shown. DETAILED DESCRIPTION
[0056] In order to more clearly illustrate the present invention, the present invention is further described below in conjunction with preferred embodiments and accompanying drawings. Similar components in the accompanying drawings are represented by the same reference numerals. It should be understood by those skilled in the art that the content specifically described below is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.
[0057] In a specific embodiment of the present invention, the structural schematic diagram of the obtained high-strength heat-insulating hollow microspheres is as follows Figure 1 The schematic diagram of its preparation process is shown in Figure 2 shown.
[0058] Example 1
[0059] A method for preparing high-strength heat-insulating hollow microspheres, the specific implementation scheme is as follows:
[0060] The density is 0.38g / cm 3 Commercial glass hollow microspheres.
[0061] (1) Flotation of glass hollow microspheres: glass hollow microspheres and water were mixed at a volume ratio of 1:4, stirred, and allowed to stand for stratification before taking out the floating microspheres on the upper layer, filtering them, and drying them to obtain hollow microspheres A.
[0062] (2) Hollow microspheres A were added to treatment solution A containing 15 g / L 3-aminopropyltriethoxysilane (the solvent was ethanol and water in a volume ratio of 2:1) at a ratio of 0.3 g / mL (0.3 g of microspheres per 1 mL of solution), stirred at room temperature for 10 min, filtered, dried at 50 °C, and then heat treated at 120 °C for 3 h to obtain hollow microspheres B.
[0063] (3) 10 g of hollow microspheres B were treated in 300 mL of treatment solution B containing 15 g / L stannous chloride, stirred at room temperature for 20 min, filtered, and dried to obtain hollow microspheres C.
[0064] (4) 2 g of hollow microspheres C were treated in 67 mL of treatment solution C containing 15 g / L silver nitrate and 8 g / L ammonia water, and then 1.1 g of formaldehyde was added dropwise under stirring. The mixture was reacted under stirring at room temperature. After the reaction was completed, the mixture was filtered and dried to obtain hollow microspheres D.
[0065] (5) 10 g nickel nitrate, 7 g citric acid and 5 g water were mixed in a beaker and stirred magnetically until completely dissolved to obtain treatment solution D;
[0066] (6) The hollow microspheres D obtained in step (4) were mixed with 2 g of treatment solution D, and then treated at 550° C. for 30 min in an air atmosphere. After the reaction, the mixture was dispersed through an 80-mesh sieve to obtain the target product: the high-strength heat-insulating hollow microspheres.
[0067] The mass percentages of the glass shell layer, the metal silver layer and the metal oxide (nickel oxide) layer in the high-strength heat-insulating hollow microspheres obtained in this embodiment are 71.4%, 21.4% and 7.2% respectively. Other structural and performance parameters are shown in Table 1.
[0068] In this specific implementation, the hollow microsphere performance test method is as follows:
[0069] 1) Density is tested using Archimedes principle;
[0070] 2) The strength is evaluated by isostatic pressing treatment, and the test is carried out according to the patent "A method for determining the isostatic strength of hollow glass microspheres" (201410196976.0);
[0071] 3) Thermal conductivity is tested using a thermal constant analyzer.
[0072] 4) The emissivity is tested using an infrared emissivity tester.
[0073] 5) The oxide particle coverage was obtained by SEM photo analysis using imageJ software.
[0074] Example 2
[0075] A method for preparing high-strength heat-insulating hollow microspheres, the specific implementation scheme is as follows:
[0076] The density is 0.38g / cm 3 Commercial glass hollow microspheres.
[0077] (1) Flotation of glass hollow microspheres: glass hollow microspheres and water were mixed at a volume ratio of 1:4, stirred, and allowed to stand for stratification before taking out the floating microspheres on the upper layer, filtering them, and drying them to obtain hollow microspheres A.
[0078] (2) Hollow microspheres A were added to treatment solution A containing 15 g / L 3-aminopropyltriethoxysilane (the solvent was ethanol and water in a volume ratio of 2:1) at a ratio of 0.3 g / mL (0.3 g of microspheres per 1 mL of solution), stirred at room temperature for 10 min, filtered, dried at 50 °C, and then heat treated at 120 °C for 3 h to obtain hollow microspheres B.
[0079] (3) 10 g of hollow microspheres B were treated in 300 mL of treatment solution B containing 15 g / L stannous chloride, stirred at room temperature for 20 min, filtered, and dried to obtain hollow microspheres C.
[0080] (4) 2 g of hollow microspheres C were treated in 135 mL of treatment solution C containing 15 g / L silver nitrate and 8 g / L ammonia water, and then 2.3 g of formaldehyde was added dropwise under stirring. The mixture was reacted under stirring at room temperature. After the reaction was completed, it was filtered and dried to obtain hollow microspheres D.
[0081] (5) 10 g nickel nitrate, 7 g citric acid and 5 g water were mixed in a beaker and stirred magnetically until completely dissolved to obtain treatment solution D;
[0082] (6) The hollow microspheres D obtained in step (4) were mixed with 2 g of treatment solution D, and then treated at 550° C. for 30 min in an air atmosphere. After the reaction, the microspheres were dispersed through an 80-mesh sieve to obtain the target product: the high-strength heat-insulating hollow microspheres. The low-magnification SEM image of the heat-insulating hollow microspheres is shown in FIG. Figure 3As shown in the high magnification SEM image Figure 4 As shown in the figure, the hollow microspheres have a perfect spherical shape, and there are a lot of wrinkles and protrusions on the surface; the enlarged SEM image shows that the surface of the microspheres (i.e. the surface of the outermost metal oxide shell) is composed of independent island particles.
[0083] The X-ray diffraction pattern of the hollow microspheres is shown in Figure 5 As shown in the figure, it can be seen that the low A peak in the small angle area is the diffraction peak of amorphous silicon dioxide (originating from the glass spherical shell), and the three sharp B peaks are the diffraction peaks of metallic silver.
[0084] The mass percentages of the glass shell layer, the metal silver layer and the metal oxide layer in the high-strength heat-insulating hollow microspheres obtained in this embodiment are 58.8%, 35.3% and 5.9% respectively. Other structural and performance parameters are shown in Table 1.
[0085] Example 3
[0086] A method for preparing high-strength heat-insulating hollow microspheres, the specific implementation scheme is as follows:
[0087] The density is 0.38g / cm 3 Commercial glass hollow microspheres.
[0088] (1) Flotation of glass hollow microspheres: glass hollow microspheres and water were mixed at a volume ratio of 1:4, stirred, and allowed to stand for stratification before taking out the floating microspheres on the upper layer, filtering them, and drying them to obtain hollow microspheres A.
[0089] (2) Hollow microspheres A were added to treatment solution A containing 15 g / L 3-aminopropyltriethoxysilane (the solvent was ethanol and water in a volume ratio of 2:1) at a ratio of 0.3 g / mL (0.3 g of microspheres per 1 mL of solution), stirred at room temperature for 10 min, filtered, dried at 50 °C, and then heat treated at 120 °C for 3 h to obtain hollow microspheres B.
[0090] (3) 10 g of hollow microspheres B were treated in 300 mL of treatment solution B containing 15 g / L stannous chloride, stirred at room temperature for 20 min, filtered, and dried to obtain hollow microspheres C.
[0091] (4) 2 g of hollow microspheres C were treated in 200 mL of treatment solution C containing 15 g / L silver nitrate and 8 g / L ammonia water, and then 3.5 g of formaldehyde was added dropwise under stirring. The mixture was reacted under stirring at room temperature. After the reaction was completed, the mixture was filtered and dried to obtain hollow microspheres D.
[0092] (5) 10 g nickel nitrate, 7 g citric acid and 5 g water were mixed in a beaker and stirred magnetically until completely dissolved to obtain treatment solution D;
[0093] (6) The hollow microspheres D obtained in step (4) were mixed with 4 g of treatment liquid D, and then treated at 550° C. for 30 min in an air atmosphere. After the reaction, the mixture was dispersed through an 80-mesh sieve to obtain the target product: the high-strength heat-insulating hollow microspheres.
[0094] The mass percentages of the glass shell layer, the metal silver layer and the metal oxide layer in the high-strength heat-insulating hollow microspheres obtained in this embodiment are 47.6%, 42.9% and 9.5% respectively. Other structural and performance parameters are shown in Table 1.
[0095] Example 4
[0096] A method for preparing high-strength heat-insulating hollow microspheres, the specific implementation scheme is as follows:
[0097] The density is 0.38g / cm 3 Commercial glass hollow microspheres.
[0098] (1) Flotation of glass hollow microspheres: glass hollow microspheres and water were mixed at a volume ratio of 1:4, stirred, and allowed to stand for stratification before taking out the floating microspheres on the upper layer, filtering them, and drying them to obtain hollow microspheres A.
[0099] (2) Hollow microspheres A were added to treatment solution A containing 15 g / L 3-aminopropyltriethoxysilane (the solvent was ethanol and water in a volume ratio of 2:1) at a ratio of 0.3 g / mL (0.3 g of microspheres per 1 mL of solution), stirred at room temperature for 10 min, filtered, dried at 50 °C, and then heat treated at 120 °C for 3 h to obtain hollow microspheres B.
[0100] (3) 10 g of hollow microspheres B were treated in 300 mL of treatment solution B containing 15 g / L stannous chloride, stirred at room temperature for 20 min, filtered, and dried to obtain hollow microspheres C.
[0101] (4) 2 g of hollow microspheres C were treated in 270 mL of treatment solution C containing 15 g / L silver nitrate and 8 g / L ammonia water, and then 5 g of formaldehyde was added dropwise under stirring. The mixture was reacted under stirring at room temperature. After the reaction was completed, the mixture was filtered and dried to obtain hollow microspheres D.
[0102] (5) 10 g nickel nitrate, 7 g citric acid and 5 g water were mixed in a beaker and stirred magnetically until completely dissolved to obtain treatment solution D;
[0103] (6) The hollow microspheres D obtained in step (4) were mixed with 6 g of treatment solution D, and then treated at 550° C. for 30 min in an air atmosphere. After the reaction, the mixture was dispersed through an 80-mesh sieve to obtain the target product: the high-strength heat-insulating hollow microspheres.
[0104] The mass percentages of the glass shell layer, the metal silver layer and the metal oxide layer in the high-strength heat-insulating hollow microspheres obtained in this embodiment are 40%, 48% and 12% respectively. Other structural and performance parameters are shown in Table 1.
[0105] Example 5
[0106] A method for preparing high-strength heat-insulating hollow microspheres, the specific implementation scheme is as follows:
[0107] The density is 0.30g / cm 3 Commercial glass hollow microspheres.
[0108] (1) Flotation of glass hollow microspheres: glass hollow microspheres and water were mixed at a volume ratio of 1:4, stirred, and allowed to stand for stratification before taking out the floating microspheres on the upper layer, filtering them, and drying them to obtain hollow microspheres A.
[0109] (2) Hollow microspheres A were added to treatment solution A containing 15 g / L 3-aminopropyltriethoxysilane (the solvent was ethanol and water in a volume ratio of 2:1) at a ratio of 0.3 g / mL (0.3 g of microspheres per 1 mL of solution), stirred at room temperature for 10 min, filtered, dried at 50 °C, and then heat treated at 120 °C for 3 h to obtain hollow microspheres B.
[0110] (3) 10 g of hollow microspheres B were treated in 300 mL of treatment solution B containing 15 g / L stannous chloride, stirred at room temperature for 20 min, filtered, and dried to obtain hollow microspheres C.
[0111] (4) 2 g of hollow microspheres C were treated in 135 mL of treatment solution C containing 15 g / L silver nitrate and 8 g / L ammonia water, and then 2.3 g of formaldehyde was added dropwise under stirring. The mixture was reacted under stirring at room temperature. After the reaction was completed, it was filtered and dried to obtain hollow microspheres D.
[0112] (5) 10 g of cobalt nitrate, 7 g of citric acid and 5 g of water were mixed in a beaker and stirred magnetically until completely dissolved to obtain a treatment solution D;
[0113] (6) The hollow microspheres D obtained in step (4) were mixed with 2 g of treatment solution D, and then treated at 550° C. for 30 min in an air atmosphere. After the reaction, the mixture was dispersed through an 80-mesh sieve to obtain the target product: the high-strength heat-insulating hollow microspheres.
[0114] The mass percentages of the glass shell layer, the metal silver layer and the metal oxide layer in the high-strength heat-insulating hollow microspheres obtained in this embodiment are 58.8%, 35.3% and 5.9% respectively. Other structural and performance parameters are shown in Table 1.
[0115] Example 6
[0116] A method for preparing high-strength heat-insulating hollow microspheres, the specific implementation scheme is as follows:
[0117] The density is 0.25g / cm 3 Commercial glass hollow microspheres.
[0118] (1) Flotation of glass hollow microspheres: glass hollow microspheres and water were mixed at a volume ratio of 1:4, stirred, and allowed to stand for stratification before taking out the floating microspheres on the upper layer, filtering them, and drying them to obtain hollow microspheres A.
[0119] (2) Hollow microspheres A were added to treatment solution A containing 15 g / L 3-aminopropyltriethoxysilane (the solvent was ethanol and water in a volume ratio of 2:1) at a ratio of 0.3 g / mL (0.3 g of microspheres per 1 mL of solution), stirred at room temperature for 10 min, filtered, dried at 50 °C, and then heat treated at 120 °C for 3 h to obtain hollow microspheres B.
[0120] (3) 10 g of hollow microspheres B were treated in 300 mL of treatment solution B containing 15 g / L stannous chloride, stirred at room temperature for 20 min, filtered, and dried to obtain hollow microspheres C.
[0121] (4) 2 g of hollow microspheres C were treated in 135 mL of treatment solution C containing 15 g / L silver nitrate and 8 g / L ammonia water, and then 2.3 g of formaldehyde was added dropwise under stirring. The mixture was reacted under stirring at room temperature. After the reaction was completed, it was filtered and dried to obtain hollow microspheres D.
[0122] (5) 14 g of ferric nitrate, 8 g of citric acid and 6 g of water were mixed in a beaker and stirred magnetically until completely dissolved to obtain a treatment solution D;
[0123] (6) The hollow microspheres D obtained in step (4) were mixed with 2 g of treatment solution D, and then treated at 550° C. for 30 min in an air atmosphere. After the reaction, the mixture was dispersed through an 80-mesh sieve to obtain the target product: the high-strength heat-insulating hollow microspheres.
[0124] The mass percentages of the glass shell layer, the metal silver layer and the metal oxide layer in the high-strength heat-insulating hollow microspheres obtained in this embodiment are 58.9%, 35.3% and 5.8% respectively. Other structural and performance parameters are shown in Table 1.
[0125] Example 7
[0126] A method for preparing high-strength heat-insulating hollow microspheres, the specific implementation scheme is as follows:
[0127] The density is 0.20g / cm 3 Commercial glass hollow microspheres.
[0128] (1) Flotation of glass hollow microspheres: glass hollow microspheres and water were mixed at a volume ratio of 1:4, stirred, and allowed to stand for stratification before taking out the floating microspheres on the upper layer, filtering them, and drying them to obtain hollow microspheres A.
[0129] (2) Hollow microspheres A were added to treatment solution A containing 15 g / L 3-aminopropyltriethoxysilane (the solvent was ethanol and water in a volume ratio of 2:1) at a ratio of 0.3 g / mL (0.3 g of microspheres per 1 mL of solution), stirred at room temperature for 10 min, filtered, dried at 50 °C, and then heat treated at 120 °C for 3 h to obtain hollow microspheres B.
[0130] (3) 10 g of hollow microspheres B were treated in 300 mL of treatment solution B containing 15 g / L stannous chloride, stirred at room temperature for 20 min, filtered, and dried to obtain hollow microspheres C.
[0131] (4) 2 g of hollow microspheres C were treated in 135 mL of treatment solution C containing 15 g / L silver nitrate and 8 g / L ammonia water, and then 2.3 g of formaldehyde was added dropwise under stirring. The mixture was reacted under stirring at room temperature. After the reaction was completed, it was filtered and dried to obtain hollow microspheres D.
[0132] (5) 10 g of copper nitrate, 7 g of sucrose and 5 g of water were mixed in a beaker and stirred magnetically until completely dissolved to obtain treatment solution D;
[0133] (6) The hollow microspheres D obtained in step (4) were mixed with 1.9 g of treatment liquid D, and then treated at 550° C. for 30 min in an air atmosphere. After the reaction, the mixture was dispersed through an 80-mesh sieve to obtain the target product: the high-strength heat-insulating hollow microspheres.
[0134] The mass percentages of the glass shell layer, the metal silver layer and the metal oxide layer in the high-strength heat-insulating hollow microspheres obtained in this embodiment are 59%, 35.1% and 5.9% respectively. Other structural and performance parameters are shown in Table 1.
[0135] Comparative Example 1
[0136] A glass-silver-oxide hollow microsphere preparation, the specific implementation scheme is as follows:
[0137] The density is 0.38g / cm 3 Commercial glass hollow microspheres.
[0138] (1) Flotation of glass hollow microspheres: glass hollow microspheres and water were mixed at a volume ratio of 1:4, stirred, and allowed to stand for stratification before taking out the floating microspheres on the upper layer, filtering them, and drying them to obtain hollow microspheres A.
[0139] (2) 10 g nickel nitrate, 7 g citric acid and 5 g water were mixed in a beaker and stirred magnetically until completely dissolved to obtain a treatment solution D;
[0140] (3) The hollow microspheres A were mixed with 2 g of treatment solution D, and then treated at 550° C. for 30 min in an air atmosphere. After the reaction, the mixture was dispersed through an 80-mesh sieve to obtain the target product, glass-oxide hollow microspheres.
[0141] The mass percentages of glass and oxide in the glass-silver-oxide hollow microspheres obtained in this comparative example are 90.8% and 9.2% respectively. Other structural and performance parameters are shown in Table 1.
[0142] Comparative Example 2
[0143] A glass-silver-oxide hollow microsphere preparation, the specific implementation scheme is as follows:
[0144] The density is 0.38g / cm 3 Commercial glass hollow microspheres.
[0145] (1) Flotation of glass hollow microspheres: glass hollow microspheres and water were mixed at a volume ratio of 1:4, stirred, and allowed to stand for stratification before taking out the floating microspheres on the upper layer, filtering them, and drying them to obtain hollow microspheres A.
[0146] (2) Hollow microspheres A were added to treatment solution A containing 15 g / L 3-aminopropyltriethoxysilane (the solvent was ethanol and water in a volume ratio of 2:1) at a ratio of 0.3 g / mL (0.3 g of microspheres per 1 mL of solution), stirred at room temperature for 10 min, filtered, dried at 50 °C, and then heat treated at 120 °C for 3 h to obtain hollow microspheres B.
[0147] (3) 10 g of hollow microspheres B were treated in 300 mL of treatment solution B containing 15 g / L stannous chloride, stirred at room temperature for 20 min, filtered, and dried to obtain hollow microspheres C.
[0148] (4) 2 g of hollow microspheres C were treated in 135 mL of treatment solution C containing 15 g / L silver nitrate and 8 g / L ammonia water, and then 2.3 g of formaldehyde was added dropwise under stirring. The mixture was reacted under stirring at room temperature. After the reaction was completed, it was filtered and dried to obtain the target product, glass-silver hollow microspheres (without oxides).
[0149] The mass percentages of glass and silver in the glass-silver hollow microspheres obtained in this comparative example are 62.4% and 37.6% respectively. Other structural and performance parameters are shown in Table 1.
[0150] Table 1 Structure and performance parameters of the hollow composite microsphere samples obtained in each embodiment
[0151]
[0152] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.
Claims
1. A high-strength heat-insulating hollow microsphere, characterized in that: The structure of the hollow microsphere comprises a hollow core, and a glass shell layer, a metal silver layer and a metal oxide layer arranged in sequence from the inside to the outside; The metal oxide layer is composed of a plurality of metal oxide regions, and the metal oxide regions are physically isolated from each other to expose a portion of the outer surface of the metal silver layer.
2. The heat insulating hollow microsphere according to claim 1, characterized in that: In the metal oxide layer, the metal oxide region is selected from one oxide of nickel, cobalt, iron, copper, zinc and aluminum or a mixture of two or more oxides.
3. The heat insulating hollow microsphere according to claim 1, characterized in that: The coverage rate of the metal oxide layer on the surface of the metal silver layer is 30-65%.
4. The heat insulating hollow microsphere according to claim 1, characterized in that: Calculated by mass percentage, the contents of the components in the hollow microspheres are: 35-75wt% of the glass shell layer, 20-50wt% of the metal silver layer, and 5-15wt% of the metal oxide layer.
5. The heat insulating hollow microsphere according to claim 1, characterized in that: The density of the hollow microspheres is 0.3-1 g / cm 3 , with an average diameter of 15-80μm.
6. The method for preparing the heat insulating hollow microspheres according to any one of claims 1 to 5, characterized in that: The steps include: The glass hollow microspheres are subjected to surface activation treatment; Assembling a metallic silver layer on the surface of the glass hollow microspheres after surface activation treatment to obtain microspheres A; A metal oxide layer is formed on the surface of microsphere A.
7. The preparation method according to claim 6, characterized in that: The method for surface activation treatment of glass hollow microspheres comprises the following steps: The glass hollow microspheres are placed in a mixture of ethanol and water containing 12-18 g / L 3-aminopropyltriethoxysilane, stirred and mixed at room temperature, filtered, dried, and then heat treated at 100-130° C. for 2-5 hours; Then, the glass hollow microspheres are placed in a 15 g / L stannous chloride aqueous solution, stirred and mixed, filtered, and dried; Preferably, the glass hollow microspheres are added to the mixed solution at a concentration of 0.3 g / mL; Preferably, the glass hollow microspheres are added to the stannous chloride aqueous solution at a concentration of 30-35 g / L.
8. The preparation method according to claim 6, characterized in that: The method for assembling a metallic silver layer on the surface of glass hollow microspheres after surface activation treatment to obtain microspheres A comprises the following steps: The glass hollow microspheres after surface activation treatment were mixed with a treatment solution containing 15 g / L silver nitrate and 8 g / L ammonia water, and then formaldehyde solution was added dropwise to react at room temperature to assemble the silver sphere shell; Preferably, the amount of the glass hollow microspheres after surface activation treatment relative to the treatment liquid is 6-30 g / L; Preferably, the amount of the formaldehyde solution relative to the treatment liquid is 15-20 g / L.
9. The preparation method according to claim 6, characterized in that: The method for forming a metal oxide layer on the surface of microsphere A comprises the following steps: The microsphere A is mixed with the reaction solution, and reacted at 400-600° C. for 30 min in an air atmosphere to obtain the heat insulating hollow microspheres; Preferably, the reaction solution contains metal salt, water-soluble organic matter and water, and the mass ratio of the microsphere A to the metal salt, water-soluble organic matter and water is (2-5):(10-15):(6-10):(5-7).
10. Use of the insulating hollow microspheres according to any one of claims 1 to 5 in powder insulation and insulating fillers.
Citation Information
Patent Citations
Method for measuring isostatic pressure resistance of hollow glass beads
CN103954506A
Cited By
Mussel bionic well wall thermal insulation material for drilling fluid as well as preparation method and application thereof
CN121064807A